2017
DOI: 10.1242/dmm.028217
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles among murine strains segregate with distinct differences in the progression of radiation-induced lung disease

Abstract: Molecular mechanisms underlying development of acute pneumonitis and/or late fibrosis following thoracic irradiation remain poorly understood. Here, we hypothesize that heterogeneity in disease progression and phenotypic expression of radiation-induced lung disease (RILD) across murine strains presents an opportunity to better elucidate mechanisms driving tissue response toward pneumonitis and/or fibrosis. Distinct differences in disease progression were observed in age- and sex-matched CBA/J, C57L/J and C57BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Most recently it was shown that depletion of interstitial macrophages (IMs) by a neutralizing antibody abrogating the CSF-CSF1R signaling inhibits RILF, whereas depletion of alveolar macrophages (AMs) by Clodrosome was not effective further underscoring the relevance of leukocyte subtypes in RILF development. 26 A brief collection of recent studies investigating potential impact of different leukocyte subsets in RILF [27][28][29][30][31][32][33][34][35][36] is provided in supplemental Table S1, Supporting Information. Segregated-nucleuscontaining atypical monocytes (SatM) with granulocyte characteristics regulated by CCAAT/enhancer binding protein β (C/EBPβ) as well as release of neutrophil extracellular traps (NETosis) consisting of extracellular chromatin orchestrated by peptidylarginine deiminase 4 (PAD4) in age related organ fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently it was shown that depletion of interstitial macrophages (IMs) by a neutralizing antibody abrogating the CSF-CSF1R signaling inhibits RILF, whereas depletion of alveolar macrophages (AMs) by Clodrosome was not effective further underscoring the relevance of leukocyte subtypes in RILF development. 26 A brief collection of recent studies investigating potential impact of different leukocyte subsets in RILF [27][28][29][30][31][32][33][34][35][36] is provided in supplemental Table S1, Supporting Information. Segregated-nucleuscontaining atypical monocytes (SatM) with granulocyte characteristics regulated by CCAAT/enhancer binding protein β (C/EBPβ) as well as release of neutrophil extracellular traps (NETosis) consisting of extracellular chromatin orchestrated by peptidylarginine deiminase 4 (PAD4) in age related organ fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, the high radio sensitivity of the normal lung tissue limits the application of curative radiation doses to the thoracic region and therapy intensification efforts of RCT (9, 11). Technical advances in image guidance and modern radiation techniques have significantly increased the safety profile of thoracic radiotherapy (1214); but radiation-induced lung disease (RILD) still represents a serious normal tissue complication associated with radio(chemo)therapy of thoracic neoplasms or total body irradiation in conditioning regimens for hematopoietic stem cell transplantation (1517). Moreover, toxicity rates can increase or new toxicities can be observed when using molecularly targeted drugs in combination with radiotherapy (1821).…”
Section: Introductionmentioning
confidence: 99%
“…The pneumonitis and fibrosis responses evident clinically have been modelled in mice, which show strain and genotype dependent presentations of these traits 13 19 . Specifically, we 13 , 15 , 16 and others 14 , 19 21 have documented that following thoracic irradiation inbred strains of mice vary in the times at which respiratory distress is evident, and at distress certain strains have developed pneumonitis, while others are prone to pneumonitis with fibrosis.Investigations of these lung response phenotypes have revealed post irradiation gene expression profiles associated with the pneumonitis and pneumonitis with fibrosis responding mouse strains 18 , 22 . Further in mouse models, we demonstrated combined toll-like receptor 2 ( Tlr2 ) and Tlr 4 deficient mice develop an enhanced fibrotic response, of earlier onset, relative to that of wild type C57BL/6J mice, in response to thoracic irradiation 17 and thus are a useful model for severe fibrosis.…”
Section: Introductionmentioning
confidence: 99%